Unveiling the Link Between Leverage and Firm Performance: A Comparative Analysis of Sharia and Non-Sharia Compliant Firms in the Indonesia Stock Exchange - Mahfirah, Titis Fatarina; Suherman, Suherman; Widyastuti, Umi; Mohidin, Rosle; Sari, Maylia Pramono; Heryana, Toni; Wastuti, Wahyu; Dewi, Monica (Journal of Business and Behavioural Entrepreneurship, 2025)
This study investigates the influence of leverage on the performance of non-financial sector companies listed on the Indonesia Stock Exchange between 2012 and 2021. The analysis is segmented into three subsets: all companies, Sharia-compliant firms, and non-Sharia-compliant firms. Leverage is gauged through four metrics: debt to total asset ratio (DAR), debt to total equity ratio (DER), short-term debt to total assets (STD), and long-term debt to total assets (LTD). Firm performance is evaluated using return on assets (ROA), return on equity (ROE), and Tobin's Q. The study employs a quantitative approach, utilizing data from publicly listed companies. Leverage and performance are quantified using the specified metrics. Statistical analyses, including regression models, are conducted to examine the relationship between leverage and performance in each of the three subsets. The primary findings indicate a negative and statistically significant correlation between leverage and firm performance, as measured by ROA and ROE, across all company subsets. However, there is a positive and statistically significant impact of leverage on Tobin's Q. A more detailed analysis within the Sharia-compliant subset reveals a negative impact of leverage on all leverage indicators concerning ROA and ROE. In contrast, within the non-Sharia-compliant subset, leverage has a negative and statistically significant influence on ROA and ROE, but a positive and statistically significant effect on Tobin's Q. These empirical findings suggest that leverage has a detrimental and statistically significant association with a firm's accounting performance, as evidenced by ROA and ROE. However, it exerts a positive and statistically significant effect on the firm's market performance, as indicated by Tobin's Q. This underscores the importance of carefully managing leverage, particularly for firms operating within the Indonesian non-financial sector, to strike a balance between accounting and market performance objectives.